Master tracks in different resolutions of Maria S. Merian cruise MSM106, Mindelo - Bremerhaven, 2022-02-26 - 2022-03-19 - Fiedler, Björn (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2022)
Raw data acquired by position sensors on board RV MERIAN during expedition MSM106 were processed to receive a validated master track which can be used as reference of further expedition data. During MSM106 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and the GPS receivers Trimble SPS855 and SAAB R4 were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.